Microhardness assessment of different commercial brands of resin composites with different degrees of translucence - Anfe, Taciana Emília de Almeida; Caneppele, Taciana Marco Ferraz [UNESP]; Agra, Carlos Martins; Vieira, Glauco Fioranelli (FapUNIFESP (SciELO), 2008)
Owing to improvements in its mechanical properties and to the availability of shade and translucence resources, resin composite has become one of the most widely used restorative materials in present day Dentistry. The aim of this study was to assess the relation between the surface hardness of seven different commercial brands of resin composites (Charisma, Fill Magic, Master Fill, Natural Look, Opallis, Tetric Ceram, and Z250) and the different degrees of translucence (translucid, enamel and dentin). Vickers microhardness testing revealed significant differences among the groups. Z250 was the commercial brand that showed the best performance in the hardness test. When comparing the three groups assessed within the same brand, only Master Fill and Fill Magic presented statistically significant differences among all of the different translucencies. Natural Look was the only one that showed no significant difference among any of the three groups. Charisma, Opallis, Tetric Ceram and Z250 showed significant differences among some of the tested groups. Based on the results found in this study, it was not possible to establish a relation between translucence and the microhardness of the resin composites assessed. Depending on the material assessed, however, translucence variation did affect the microhardness values of the resin composites.
Keywords: Color; Composite resins; Hardness; resin; analysis of variance; chemistry; color; colorimetry; dental surgery; hardness; materials testing; nonparametric test; surface property; Analysis of Variance; Colorimetry; Composite Resins; Dental Restoration, Permanent; Materials Testing; Statistics, Nonparametric; Surface Properties